Nursing Diagnoses and Interventions in the Field of Action for Patients Undergoing Renal Replacement Therapy: A Scoping Review - Miguel Angel Cuevas‐Budhart; José Ramón Paniagua Sierra; Renata Cedillo‐Flores; Sonsoles Hernandez‐Iglesias; Almudena Crespo Cañizarez; Maria Alina Renghea; José Antonio Herrero Calvo; Vicente Beneit Montesinos; Mercedes Gómez Del Pulgar G (Nursing Open)
ABSTRACT Aim To identify the primary nursing diagnoses and interventions related to patients with chronic kidney disease undergoing renal replacement therapy, organised according to Marjory Gordon's functional health patterns through a scoping review. Methods A scoping review was conducted following the JBI 2020 Guidelines and the PRISMA ScR extension. Articles published between 2014 and 2021 were included from the Web of Science, Scopus and PubMed databases. The search strategy utilised DeCS and MeSH descriptors with Boolean operators AND/OR. Articles in English and Spanish authored by nurses and featuring retrospective, prospective or cross‐sectional designs were selected. After extracting the main diagnoses and interventions, a nominal group of nephrology experts discussed the findings, followed by a Delphi technique to achieve consensus. Results A total of nine studies were included, eight from Brazil and one from Turkey, which reflects a possible geographic concentration bias. Fifty‐five nursing diagnoses and seventy‐six core interventions were identified and categorised into Marjory Gordon's 11 functional patterns, facilitating the structuring of nursing action fields in nephrology. Conclusions This review established a set of standardised nursing interventions specific to patients with chronic kidney disease undergoing renal replacement therapy. Implications for health policies: The classification supports the organisation of nephrology units, reduces professional overload and enhances care quality and patient safety. The standardised taxonomy (NANDA, NIC, NOC) facilitates interdisciplinary communication and promotes advanced nursing practice. No Patient or Public Contribution The study is a review of already published scientific articles and a review of experts and researchers who contributed to the document. For this reason, an express declaration of the patient, user or caregivers is not required since there was no participation in the study.